The transcriptome of metamorphosing flatfish - Alves, Ricardo N. (2016)
Background Flatfish metamorphosis denotes the extraordinary transformation of a symmetric pelagic larva into an asymmetric benthic juvenile. Metamorphosis in vertebrates is driven by thyroid hormones (THs), but how they orchestrate the cellular, morphological and functional modifications associated with maturation to juvenile/adult states in flatfish is an enigma. Since THs act via thyroid receptors that are ligand activated transcription factors, we hypothesized that the maturation of tissues during metamorphosis should be preceded by significant modifications in the transcriptome. Targeting the unique metamorphosis of flatfish and taking advantage of the large size of Atlantic halibut (Hippoglossus hippoglossus) larvae, we determined the molecular basis of TH action using RNA sequencing. Results De novo assembly of sequences for larval head, skin and gastrointestinal tract (GI-tract) yielded 90,676, 65,530 and 38,426 contigs, respectively. More than 57 % of the assembled sequences were successfully annotated using a multi-step Blast approach. A unique set of biological processes and candidate genes were identified specifically associated with changes in morphology and function of the head, skin and GI-tract. Transcriptome dynamics during metamorphosis were mapped with SOLiD sequencing of whole larvae and revealed greater than 8,000 differentially expressed (DE) genes significantly (p < 0.05) up- or down-regulated in comparison with the juvenile stage. Candidate transcripts quantified by SOLiD and qPCR analysis were significantly (r = 0.843; p < 0.05) correlated. The majority (98 %) of DE genes during metamorphosis were not TH-responsive. TH-responsive transcripts clustered into 6 groups based on their expression pattern during metamorphosis and the majority of the 145 DE TH-responsive genes were down-regulated. Conclusions A transcriptome resource has been generated for metamorphosing Atlantic halibut and over 8,000 DE transcripts per stage were identified. Unique sets of biological processes and candidate genes were associated with changes in the head, skin and GI-tract during metamorphosis. A small proportion of DE transcripts were TH-responsive, suggesting that they trigger gene networks, signalling cascades and transcription factors, leading to the overt changes in tissue occurring during metamorphosis.